The Future of Care: What is the Future of AI in Nursing? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Introduction: The Digital Transformation of Nursing The integration of Artificial Intelligence (AI) in nursing represents one of the most significant sh...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care